Variants Disrupting CD40L Transmembrane Domain and Atypical X-Linked Hyper-IgM Syndrome: A Case Report With Leishmaniasis and Review of the Literature - Palterer, Boaz; Salvati, Lorenzo; Capone, Manuela; Mecheri, Valentina; Maggi, Laura; Mazzoni, Alessio; Cosmi, Lorenzo; Volpi, Nila; Tiberi, Lucia; Provenzano, Aldesia; Giglio, Sabrina; Parronchi, Paola; et al. (Frontiers in Immunology, 2022)
The X-linked Hyper-IgM (XHIGM) syndrome is caused by mutations of the CD40LG gene, encoding the CD40L protein. The clinical presentation is characterized by early-onset infections, with profound hypogammaglobulinemia and often elevated IgM, susceptibility to opportunistic infections, such as Pneumocystis jirovecii pneumonia, biliary tract disease due to Cryptosporidium parvum and malignancy. We report a 41 years-old male presenting with recurrent leishmaniasis, hypogammaglobulinemia, and myopathy. Whole-exome sequencing (WES) identified a missense variant in the CD40LG gene (c.107T>A, p.M36K), involving the transmembrane domain of the protein and a missense variant in the carnitine palmitoyl-transferase II (CPT2; c.593C>G; p.S198C) gene, leading to the diagnosis of hypomorphic XHIGM and CPT2 deficiency stress-induced myopathy. A review of all the previously reported cases of XHIGM with variants in the transmembrane domain showcased that these patients could present with atypical clinical features. Variants in the transmembrane domain of CD40LG act as hypomorphic generating a protein with lower surface expression. Unlike large deletions or extracellular domain variants, they do not abolish the interaction with CD40, therefore preserving some biological activity.